The glymphatic system: Current understanding and modeling - Bohr, Tomas; Hjorth, Poul G.; Holst, Sebastian C.; Hrabětová, Sabina; Kiviniemi, Vesa; Lilius, Tuomas; Lundgaard, Iben; Mardal, Kent-Andre; Martens, Erik A.; Mori, Yuki; Nägerl, U. Valentin; Nicholson, Charles; et al. (iScience, 2022)
We review theoretical and numerical models of the glymphatic system, which circulates cerebrospinal fluid and interstitial fluid around the brain, facilitating solute transport. Models enable hypothesis development and predictions of transport, with clinical applications including drug delivery, stroke, cardiac arrest, and neurodegenerative disorders like Alzheimer’s disease. We sort existing models into broad categories by anatomical function: Perivascular flow, transport in brain parenchyma, interfaces to perivascular spaces, efflux routes, and links to neuronal activity. Needs and opportunities for future work are highlighted wherever possible; new models, expanded models, and novel experiments to inform models could all have tremendous value for advancing the field. [Display omitted] Neuroscience; Neuroanatomy; Systems biology